Hidden climate change related risks for the private sector - Annette Brunsmeier; Markus Groth (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
Climate change related risks impact and challenge the private sector in many different ways. This also applies to risk drivers like a companies' reputation and a changing consumer behavior. Since significant risk drivers for companies differ just as much as companies themselves, a sector specific guideline to evaluate possible climate change related risk drivers is indispensable. Further, a sector specific analysis on these risk drivers can foster cross sectoral cooperation, innovation and learning processes with regard to climate change related risks.
Keywords: D12; L19; L20; L60; L70; L80; L90; Q40; Q51; Q54; Q59; 330; business sectors; CDP; climate change adaptation; climate change impacts; companies' reputation; consumer behavior; industry studies; risk drivers